Understanding the role of the ‘self’ in the social priming of mimicry - Wang, Yin; Hamilton, Antonia F. de C. (Public Library of Science, 2013)
People have a tendency to unconsciously mimic other's actions. This mimicry has been regarded as a prosocial response which increases social affiliation. Previous research on social priming of mimicry demonstrated an assimilative relationship between mimicry and prosociality of the primed construct: prosocial primes elicit stronger mimicry whereas antisocial primes decrease mimicry. The present research extends these findings by showing that assimilative and contrasting prime-to-behavior effect can both happen on mimicry. Specifically, experiment 1 showed a robust contrast priming effect where priming antisocial behaviors induces stronger mimicry than priming prosocial behaviors. In experiment 2, we manipulated the self-relatedness of the pro/antisocial primes and further revealed that prosocial primes increase mimicry only when the social primes are self-related whereas antisocial primes increase mimicry only when the social primes are self-unrelated. In experiment 3, we used a novel cartoon movie paradigm to prime pro/antisocial behaviors and manipulated the perspective-taking when participants were watching these movies. Again, we found that prosocial primes increase mimicry only when participants took a first-person point of view whereas antisocial primes increase mimicry only when participants took a third-person point of view, which replicated the findings in experiment 2. We suggest that these three studies can be best explained by the active-self theory, which claims that the direction of prime-to-behavior effects depends on how primes are processed in relation to the ‘self’.